An Overview on Solar Thermal Energy for Cooling and Air Con’ditioning - Ajib, Salman (Annals of Arid Zone, 2016)
Over the last few years there has been increase in the researches on solar thermal cooling installations especially the producers of solar thermal collectors and systems were looking for thermal chillers for domestic use. Several test prototypes and commercial absorption and adsorption chillers for solar cooling with refrigeration capacity ranging from with 2 kW to 15 kW have been developed. Most of the developed absorption chillers have H20/LiBr as working solution. The developed adsorption chillers have either water/silica-gel or water Zeolite as working pairs. Furthermore, there are some developments for solar assisted desiccant cooling systems with capacity of more than 100 kW. These systems have shown scope for standardization and commercialization so as to replace partly the conventional ones with much saving in primary energy. The investing costs are at present higher than the conventional one, but the operating costs are less. The Coefficient of Performance (COP) depends on system type, working temperatures and conditions as well as on the refrigeration capacity of the systems. Moreover, COP ranges between 0.4 and 1.2. In this connection an overview of solar thermal energy for cooling and air conditioning is presented considering energetic economic point of views and compared with the conventional compression systems. Furthermore, some investigation results on solar thermally driven systems, in the small and middle refrigeration capacity ranges (5-15kW) are shown. Finally, some optimization possibilities for such systems are suggested and the perspectives illustrated. Key words: Absorption, adsorption, refrigeration systems, solar thermal energy, heat and mass transfer, energetic and economic comparison.